Non‐viral suicide gene therapy in cervical, oral and pharyngeal carcinoma cells with CMV‐ and EEV‐plasmids. (3rd October 2018) - Düzgüneş, Nejat; Cheung, Jennifer; Konopka, Krystyna
Abstract: Background: Cervical cancer is the third most common cause of cancer in women. The 5‐year survival rate in oropharyngeal squamous cell carcinomas is approximately 50% and this rate has not improved in recent decades. These cancers are accessible to direct intervention. We examined the ability of a highly efficient non‐viral vector, TransfeX (ATCC, Manassas, VA, USA), to deliver the suicide gene HSV‐ tk to cervical, oral and pharyngeal cancer cells and to induce cytotoxicity following the administration of the prodrug, ganciclovir. Methods: HeLa cervical carcinoma, HSC‐3 and H357 oral squamous cell carcinoma and FaDu pharyngeal carcinoma cells were transfected with cytomegalovirus (CMV)‐ or enhanced episomal vector (EEV)‐driven HSV‐ tk plasmids and treated with ganciclovir for 24–120 h. Cell viability was assessed by Alamar blue. Results: The viability of HeLa cells was reduced to only 30–40%, despite the very high levels of transgene expression. By contrast, the viability of HSC‐3 cells was reduced to 10%, although transgene expression was 18‐fold lower than that in HeLa cells. An approximately five‐fold higher transgene expression was obtained with the EEV‐plasmid than from the CMV‐plasmid. Nevertheless, HeLa cell viability after suicide gene + ganciclovir treatment was reduced by only 35% compared to 70% with the CMV‐plasmid. For HSC‐3 cells, the reduction was 40% for the EEV‐ and 80% for the CMV‐plasmid. The lower efficiency of transfection with the EEV‐plasmid may explain the lower cytotoxicity. Conclusions: TransfeX‐mediated gene delivery to cervical, pharyngeal and oral cancer cells may be used for suicide gene therapy. The levels of transgene expression, however, do not translate directly to cytotoxicity.